Clinical and angiographic characteristics of patients with familial hypercholesterolemia presenting with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention - Khaled M. Elmaghraby; Ahmed Abdel-Galeel; Amira Harby Osman; Hosam Hasan-Ali; Mohamed Aboel-Kassem F. Abdelmegid (Scientific Reports)
Abstract Familial hypercholesterolemia (FH) is a world public health problem that enhances the risk of premature coronary artery disease (CAD) with a high incidence of acute coronary syndrome. This study aimed to evaluate the clinical and angiographic characteristics of the patients with and without FH who had ST-elevation myocardial infarction (STEMI). It included 690 patients who presented with the first attack of STEMI and underwent primary percutaneous coronary interventions (PPCI). The patients were analyzed to diagnose FH according to the Dutch Lipid Clinic Network (DLCN) criteria. All angiograms were analyzed for the number of diseased vessels, Syntax score, thrombus burden grade, and final Thrombolysis in Myocardial Infarction (TIMI) flow grade. The majority of patients were male (72.6%) with a mean age of 54 ± 12 years. Based on DLCN criteria, they were classified into unlikely/possible FH (86.1%) and probable/definite FH (13.9%) groups. Probable/definite FH patients were significantly younger, and higher incidence of males < 55 years compared with unlikely/possible FH patients (p < 0.001 for each). Moreover, probable/definite FH patients had a higher frequency of three-vessel disease (p = 0.007) and Syntax score (p < 0.001) with a moderate positive correlation with the DLCN score (r = 0.592, p < 0.001). Furthermore, probable/definite FH patients showed a higher thrombus burden and final TIMI slow/no-reflow when compared to the unlikely/possible FH patients (p = 0.006 and p = 0.027, respectively). Patients with probable/definite FH and LDL-C level were independent predictors of high thrombus burden besides males < 55 years, and the number of diseased vessels. In conclusion, STEMI patients with FH were younger males and associated with severe CAD with frequent multivessel CAD, high anatomical complexity of CAD, and frequent high thrombus burden. Furthermore, FH was one of the predictors of high thrombus burden.